The influence of Work Environment, Job Satisfaction, and Organizational Commitment on Employee Performance at PT Sun Star Motor Branch MT Haryono Semarang - Nanda Dania Ariani Widyastuti; Fatchun - Hasyim; Suharmanto - Suharmanto (Politeknik Negeri Semarang, 2020)
Employee performance of PT Sun Star Motor is affected by many factors. This research aims to analiyze the influence of work environment, job satisfaction, and organizational commitment on employee performance at PT Sun Star Motor Branch MT Haryono Semarang. The technique of analysis used is multiple linear regression. The population and sample are the entire of employees of PT Sun Star Motor Branch MT Haryono is 40 people. Data collection method used are questionnaire, participant observation and literature review. The results of F-test, shows that work environment, job satisfaction, and organizational commitment has significant affect on employee performance at PT Sun Star Motor Branch MT Haryono Semarang. Based on the results of the t test, the work environment has a significant positive effect on the employee performance of PT Sun Star Motor Branch MT Haryono Semarang. Job satisfaction has no significant effect on employee performance at PT Sun Star Motor Branch MT Haryono Semarang. And organizational commitment has significant positive effect on employee performance at PT Sun Star Motor Branch MT Haryono Semarang. While the coefficient of determination (adjusted R2) of employee performance is 61.8% which is explained by work environment, job satisfaction, and organizational commitment. The remaining 38.2% is influenced by other factors outside the model